Screening of proteolytic bacteria from the intestines of Tilapia Fish (Oreochromis niloticus) in the mina padi area of ​​Panembangan Village, Cilongok. - Syifa Febrianti, Naily; Kasprijo, Kasprijo; Zainuddin, Muhammad; Muhammad Riady, Reza (PT. Artha GenetikaLab Indonesia, 2025)
Tilapia is a commodity cultivated in the rice-fish farming area of Panembangan, Banyumas. Information related to the presence of potential bacteria in the intestines of fish cultivated in rice-fish areas is still low, especially proteolytic bacteria. The purpose of this study was to determine the proportion and activity index of proteolytic bacteria in the intestines of fish. This study used an observation method with a purposive sampling technique. Proteolytic bacteria were isolated from the intestines of tilapia in blocks A and E. The bacteria that were successfully isolated were grown on 2% skim milk agar media with an incubation time of 48 hours and observed at 24-hour intervals. Based on the results of the study, the proportion of proteolytic bacteria in the intestines of tilapia from both blocks was 28% in block A and 44% in block E, respectively. The proteolytic activity index of both blocks had an average of 0.48 for block A and 0.75 for block E. The highest proteolytic activity index was from block A, namely 0.83, and in block E 3.0. Meanwhile, the smallest proteolytic index is 0.17 block E and 0.22 block A.